The Activist, the Ideologist and the Researcher. On "Guesstimates" and Trafficking in Women - Jean Michel Chaumont (Nordicum-Mediterraneum, 2014)
A few months ago, an old and well-respected friend of mine invited me to join the local branch of ATTAC, which takes a very strong position on the topic of trafficking, as it was published in "Globalization of Prostitution, a Global Threat to Human Dignity." How reliable are its sources, though?